Numerical Simulation of the Thermo-catalytic Reforming Process: Up-scaling Study - Elmously, Mohamed; Neidel, Johannes; Apfelbacher, Andreas; Daschner, Robert; Hornung, Andreas (Industrial & Engineering Chemistry Research, 2021)
The up-scaling of the pyrolysis technologies is the next step to achieve the industrial scale and to fulfill the energy and petrochemical demand in large-scale units. The overall goal of this study is to up-scale the Thermo-Catalytic Reforming (TCR) technology from the laboratory to the pilot unit. In the previous part of the study, the up-scaling was studied experimentally in regard to the product yields and qualities. Therefore, a computational fluid dynamics (CFD) study is carried out to investigate the effects of up-scaling of the TCR system on the temperature distribution through the intermediate pyrolysis and the catalytic reforming process. A multifluid model and K-ϵ model are employed to simulate the TCR process for the mixture flow of sewage sludge as a solid phase and pyrolysis vapor as a gas phase. The results reveal a CFD model that can predict the heat distribution and flow velocities through the TCR system, while the deviations between simulation data and experimental work are considered small. The errors in the maximum biomass temperature within the auger reactor are 0.0 and 4.2% for TCR2 and TCR30, and the deviations in the solid residence time are about 0.8 and 0.74 s, respectively. Furthermore, the deviations in the vapor residence time within the post-reformer are 0.35 and 0.81 s for TCR2 and TCR30, respectively. Additionally, the CFD model provides a good platform for further simulation of the chemical reaction kinetics.
CRIS-Team Scopus Importer:2021-04-16

Thermo-Catalytic Reforming of Biological Waste and Woody Biomass Residues - Elmously, Mohamed; Neidel, Johannes; Apfelbacher, Andreas; Daschner, Robert; Hornung, Andreas (28th European Biomass Conference and Exhibition (EUBCE)-2020, 2020)
The bio-refinery is an important approach to alternative energy generation. The pyrolysis technology has a great potential for the conversion of different biomass wastes into bio-fuels. The aim of the present work is to investigate the potentials of different categories of biomass waste for bio-fuels production by Thermo-catalytic reforming technology (TCR ® ). TCR ® is an intermediate pyrolysis combined with an additional post-reforming, while the in the post-reformer, the produced char acts as a catalyst at high temperatures range up to 700 ° C. The experiments have been carried out in a laboratory scale plant under the following conditions: intermediate pyrolysis at 400 ° C and reforming at 700 ° C. The trails have been carried out with low ash containing feedstock such as woody biomass, olive waste, spent coffee grounds, and feed materials with high ash content like digestate and sewage sludge. The results show that the TCR ® technology has a great potential for the conversion of different biomass wastes into high quality bio-oil and clean and hydrogen rich syngas. In general, the products distribution and qualities are depending on the ash content and the initial organic compounds in the feedstoc
Keywords: Intermediate Pyrolysis; TCR®; woody biomass; biological waste

Thermo-Catalytic Reforming of spent coffee grounds - Elmously, Mohamed; Jäger, Nils; Apfelbacher, Andreas; Daschner, Robert; Hornung, Andreas (Bioresources and Bioprocessing, 2019)
Conversion of spent coffee grounds through the Thermo-Catalytic Reforming system (TCR®) is evaluated in this study. While, the TCR® is a technology that has been developed by Fraunhofer UMSICHT, which combines an intermediate pyrolysis and a catalytic reforming. The temperature of the catalytic reformer is varied between 500 and 700 °C to achieve an optimum yield quantities and qualities of the products. The hydrogen concentration is maximized at a reforming temperature of 700 °C, and a gas yield up to 52 wt% is achieved. The thermal stable bio-oil produced at 700 °C has the highest calorific value of 36.8 MJ/kg with significantly low oxygen and water content, low viscosity and low TAN (total acid number). Furthermore, the maximum bio-oil and char yields are obtained at the lowest reforming temperature of 500 °C. Overall spent coffee grounds show a great potential as feedstock in the Thermo-Catalytic Reforming for energy and bio-chemicals production.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-12-03
Keywords: Catalytic reforming; Intermediate pyrolysis; Spent coffee grounds; Sustainable fuels; TCR

Upscaling of Thermo-Catalytic Reforming Process from Lab to Pilot Scale - Elmously, Mohamed; Jäger, Nils; Neidel, Johannes; Apfelbacher, Andreas; Daschner, Robert; Hornung, Andreas (Industrial & Engineering Chemistry Research, 2019)
Biomass has become an important approach to meet the current requirements of energy and oil alternatives. In recent years, extensive research has been carried out on the transformation of biological wastes into biofuels and biorefineries through pyrolysis, which may gradually be replacing the crude-oil resources. One promising pyrolysis route is intermediate pyrolysis, which opens the field to the valorization of a high variety of biological residues into biofuels including gases, liquid chemicals, and carbonizate. In the present work, the Thermo-Catalytic Reforming (TCR) technology based on intermediate pyrolysis with integrated catalytic reforming is discussed, showing high productivity and higher quality biofuels compared to traditional pyrolysis systems. This paper illustrates the data from the upscaling of the TCR system from laboratory scale to pilot scale using sewage sludge as feedstock. The effects of the design differences are studied from the point of view of the qualities of products, mass, and energy balances of the laboratory unit upon the pilot unit.
CRIS-Team Scopus Importer:2019-06-28